Plasmonics: Hybrid Graphene–Giant Nanocrystal Quantum Dot Assemblies with Highly Efficient Biexciton Emission (Advanced Optical Materials 1/2015). Issue 1 (January 2015) - Gao, Yongqian; Roslyak, Oleksiy; Dervishi, Enkeleda; Karan, Niladri S.; Ghosh, Yagnaseni; Sheehan, Chris J.; Wang, Feng; Gupta, Gautam; Mohite, Aditya; Dattelbaum, Andrew M.; Doorn, Stephen K.; Hollingsworth, Jennifer A.; et al.
<x xml:space="preserve">Abstract</x> When giant nanocrystal quantum dots (g‐NQDs) are coupled to graphene, pairs of excitons optically excited in the g‐NQDs experience efficient recombination and subsequent simultaneous emission of photon pairs. This enhancement is provided by a localized plasmon supported by a charge puddle that forms underneath the photocharged g‐NQD. On page 39, H. Htoon and co‐workers reveal the tremendous potential of graphene‐g‐NQD hybrids for lasing and entangled photon source applications. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>